Faktor-Faktor yang Mempengaruhi Pemanfaatan Layanan BPJS Kesehatan pada Masyarakat: Factors Influencing the Utilization of BPJS Health Services in the Community - Rusmayadi; David Haryanto; Evi Gustia Kesuma (MPI Press, 2026)
Introduction: The National Health Insurance program (JKN), administered through BPJS Kesehatan, plays a crucial role in improving access to equitable and quality health services. However, the utilization of BPJS services remains uneven, particularly in rural areas such as Labuhan Sumbawa, where various structural and individual barriers still exist.Objectives: This study aims to identify the factors influencing the utilization of BPJS Kesehatan services and to analyze the relationship between these factors and service utilization among the community in Labuhan Sumbawa.Method: This study employed a quantitative approach with an analytical cross-sectional design. Data were collected from randomly selected respondents using a structured questionnaire that measured socio-demographic characteristics, financial status, knowledge, membership status, and perceived service complexity. Data analysis included univariate and bivariate tests using the Chi-square method to assess relationships between variables.Result: The findings indicate that financial status is the most dominant factor influencing the utilization of BPJS Kesehatan services. Other contributing factors include limited understanding of BPJS procedures, inactive membership status, and perceptions of complex administrative processes. Statistical analysis demonstrates a significant relationship between these factors and the utilization of BPJS services, indicating that both economic and non-economic aspects play an important role in shaping health service utilization behavior.Conclusion: The utilization of BPJS Kesehatan services is influenced by an interplay of financial capacity, knowledge, and perceived service accessibility. Strengthening health literacy, improving administrative simplicity, and ensuring economic affordability are essential strategies to enhance service utilization. These findings highlight the need for integrated policy interventions to optimize the effectiveness of the national health insurance program.